2011
DOI: 10.1016/j.ypmed.2011.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and efficacy of pairing fecal immunochemical testing with mammography for increasing colorectal cancer screening among uninsured Latinas in northern Manhattan

Abstract: This study suggests that pairing CRC education and screening with mammography is both feasible and efficacious.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 43 publications
0
24
1
Order By: Relevance
“…These results are in contrast to previous observational research that has shown that acculturation to the US is positively related with the use of preventive and cancer screening services [7, 1519, 24–26]. However, studies conducted in the context of a patient navigation programs have shown that acculturation to the US is negatively correlated with CRCS [14, 27]. In other words, it is likely that less acculturated individuals, who prefer Spanish and more recently immigrated, are more likely to adhere to colonoscopy guidelines than more acculturated individuals if they receive a recommendation for screening and patient navigation services.…”
Section: Discussioncontrasting
confidence: 95%
“…These results are in contrast to previous observational research that has shown that acculturation to the US is positively related with the use of preventive and cancer screening services [7, 1519, 24–26]. However, studies conducted in the context of a patient navigation programs have shown that acculturation to the US is negatively correlated with CRCS [14, 27]. In other words, it is likely that less acculturated individuals, who prefer Spanish and more recently immigrated, are more likely to adhere to colonoscopy guidelines than more acculturated individuals if they receive a recommendation for screening and patient navigation services.…”
Section: Discussioncontrasting
confidence: 95%
“…For example, if rural patients are more burdened with competing demands, structural barriers to accessing care (e.g., transportation), and costs of care, then systems may need to prioritize FOBT/FIT with colonoscopy follow-up on abnormal tests. Launching FOBT/FIT kit campaigns may be particularly impactful in addressing screening disparities in rural and Medicaid populations as they help reduce structural and geographic barriers to CRC screening and have demonstrated effectiveness and cost-effectiveness in these populations (Briant et al, 2015; Charlton et al, 2014; Hillyer et al, 2011; Coronado et al, 2011; Gupta et al, 2013b). …”
Section: Discussionmentioning
confidence: 99%
“…MailedFIT was the main intervention and had the most impact in increasing screening; FluFIT, MammoFIT, and 50th birthday mailings had a limited reach to smaller patient cohorts. The supplemental offering of FIT kits during flu shot clinics and mammography screening events resulted in more than one‐half of individuals returning the kits and could be a cost‐effective approach …”
Section: Discussionmentioning
confidence: 99%
“…The supplemental offering of FIT kits during flu shot clinics and mammography screening events resulted in more than one-half of individuals returning the kits and could be a cost-effective approach. 16,17 Overall, nearly one-third of patients who were due for screening successfully participated in the FIT program. Despite potential facilitators, such as receiving mailings in their preferred language and wordless instructions, most of those who received the FIT kits did not complete the screenings.…”
Section: Discussionmentioning
confidence: 99%